THE BLOOD PRESSURE MEASUREMENTS TAKEN BY BOTH DOCTORS AND NURSES IN THE SAME ENVIRONMENT: DIFFERENCES AND INFORMATION. (June 2018) - Nazzaro, P.; Vitali, I.; Laselva, G.; Nardecchia, A.; Moscatelli, F. Caradonna; Contini, M.; Schirosi, G.; De Benedittis, L.; Aceto, G.; Papagni, A.M.
Abstract : Objective: Blood pressure (BP) surge during medical visit represents a phenomenon associated to vascular damage but little is known on implication of BP change measured by nurse and doctor in the same medical setting. Aim of the study was to discern the association of different indices of vascular damage and cognitive impairment with the different BP measures in hypertensives treated with ARBs or ACEi as monotherapy. Design and method: In the same day, hours (08.00–11.30 a.m.) and medical controlled environment, by the same sphygmomanmeter (Microlife Afib), 226 grade 1–2 hypertensives with similar age, education, metabolic and hypertensive state, were visited. After ambulatory blood pressure monitoring (day/night), they underwent to BP measurement by the nurse (lab) and the doctor (doc), general cognitive impairment (COGtot) by 18-items (NPI) and, by carotid intima-media thickness (IMT) and carotid-femoral pulse wave velocity (PWVcf), assessment of preclinical, structural and functional, vascular damage. Results: : Patients, subdivided in tertiles by the SBPdoc-lab difference, reduced (R), intermediate (M) and elevated (E), showed significant differences (m ± s.d.; *:p < .05, **:p < .01, ***:p < .001 vs SBPdoc-labR; °:p < .05, °°:p < .01, °°°:p < .001 vs SBPdoc-labM). Figure. No caption available. SBPdoc-labE patients demonstrated a higher total cognitive deficit score, particularly, brief-term memory (NPI3) and phrontal cortex activity (NPI4, NPI5) impairment. Pearson analysis, adjusted for age and history of hypertension, showed the association between SBPdoc-lab and PWV (.193*), NPI3 (.148*) and COGtot (.137*). The BP surge during the medical examination, mostly due to the doctor visit, seems to be associated to the onset to functional preclinical vascular damage in patients with similar circadian profile. Conclusions: The findings showed that brief-term BP changes, ascertained in a controlled environment by standardized methods, particularly the changes ascribable to the "white-coat effect", might be predictive of preclinical vascular damage and, then, of cardiovascular prognosis.